A better place to play: Public support and spatial patterns of firm relocation in Europe - Anabela Marques Santos; Francesco Lelli; Francesco Molica (European Commission, Joint Research Centre (JRC), 2025)
This paper explores the spatial patterns associated with large-scale relocation events in the European Union. It examines both relocation within national borders and delocalisation across countries, using data from 2002 to 2023 at the NUTS2 level. The study draws on Eurofound's European Restructuring Monitor (ERM) dataset and applies Probit and Poisson regression models to identify key regional characteristics linked to these events. The findings suggest that cost efficiency plays a central role in driving both types of relocation. Regions with greater access to Cohesion Policy funds tend to experience fewer internal relocations, while a higher availability of State aid is associated with a lower incidence of cross-border delocalisations. The analysis also indicates that manufacturing sectors - particularly electronics, automotive, and computer industries - are most frequently affected, likely due to the nature of their production processes. Moreover, such relocation dynamics appear more dominant in more developed regions, possibly due to the cost advantages offered by less developed regions.
Keywords: L16; H71; R12; 330; Relocation; Delocalisation; European funds; European Union